(untitled) (Journal of Pedagogical Inventions and Practices, 2024)
In the realms of exact and natural sciences, empirical experimentation forms the cornerstone of profound understanding and advancements. This intrinsic dependence on experimental validation underscores the indispensable role of laboratory work as a complementary and integral format of practical exploration. This article aims to delineate the systematic methodology employed in conducting experimental research within the domains of thermodynamics and thermal engineering, providing insights into the procedural sequence that ensures the integrity and reproducibility of scientific investigations in these fields